Chromatographic and electrophoretic techniques. - Smith, Ivor (William Heinemann Medical Books Ltd. ; Interscience Publishers, Inc., 1960)
Chromatography and Electrophoretic Techniques, Volume II: Zone Electrophoresis presents a number of methods, all based on zone electrophoresis, which has been carried out on commercially available apparatus offering many advantages to the majority of laboratories. This book is composed of six chapters and begins with discussions on the principles, instrumentation, and applications of paper electrophoresis at low voltages, such as voltages not exceeding 300-400 volts or a potential drop of not more than 10 volts/cm in the direction of migration. The next chapter describes the general experiment.